Characteristics of immunologic markers in pediatric acute lymphoblastic leukemia with genetic mutation at National Institute of Hematology and Blood Transfusion from 2016 to 2018 - Hong, Hoang Thi; Lan, Mai; Tung, Nguyen Quang; Van, Nguyen Trieu; Khanh, Bach Quoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Determining characteristic of immune classification and genetic mutations plays an important role in diagnosis, treatment and prognosis of pediatric ALL. Objective: Research on characteristic of cluster of differentiation in peadiatric ALL with genetic mutations in National institute of Hematology and Blood transfusion from 2016-2018. Methods: Cross-sectional descriptive on 189 pediatric patients aged 1-15 years old with newly diagnosis ALL. Results. Frequency of fusion genes was 26.9% (fusion gene TEL-AML1 13.2%, BCR-ABL 8.5%, E2APBX1 2.6%, MLL-AF4 2.6%). B - ALL was prevalent with 82.0%; T - ALL accounted for 16.4%. 97,8% of the patients with genetic mutation were in group of B-ALL. CD45 showed strong positive expression in most of the groups; The rate of HLA-DR imprints was high in genetically modified groups. The incidence of CD34 patients was highest in the BCR-ABL1 fusion gene group. The E2A-PBX1 gene mutation group was negative for CD34. The presence of CD19, CD79a markers was high in pediatric patients. CD10 (+) was low in the MLL-AF4 group. The incidence of CD20 was low in the groups. The incidence of myeloid CD was highest in BCR-ABL1 (37.5% positive for CD33), without the presence of myeloid CD in the pediatric patients with the E2A- PBX1 and MLL-AF4 fusion gene.